How Bruce Lee changed the world [videorecording (DVD)] - Webb, Steve; Parnell, Charles (A & E Television Networks : Distributed by New Video, 2009)
With his lightining-quick hands and feet, steely body, and vast knowledge of martial arts, Bruce Lee was a one-of-a-kind powerhouse. He took on and out the bad guys with gusto. His astonishing skills brought him fame and movie roles. Learn the whole story from his birth in San Francisco to his mysterious death - some say the result of a curse - at the age of 32, just three weeks before the opening of his only U.S. film, "Enter the dragon." Along the way, Lee introduced ancient martial arts to the modern world, securing a permanent place in our popular culture. Contains seldom-seen interviews and rare home movies. Hear from those he influenced, from Jackie Chan to John Woo, Brett Ratner, LL Cool J and Stan Lee.